PROFITABILITY, LIQUIDITY, SALES GROWTH, FIRM SIZE : FINANCIAL DISTRESS WITH LEVERAGE AS A MODERATING VARIABLE - Nurkhasannah, Meylia; Nawirah, Nawirah (Jurnal Edueco, 2025)
This study seeks to investigate how profitability, liquidity, sales growth, and firm size affect financial distress, with leverage serving as a moderating factor. The research utilizes panel data regression analysis through E-Views 12. The sample includes 111 companies from the raw material sector that are traded on the Indonesia Stock Exchange (IDX) from 2021 to 2023 Financial reports available on the IDX website were used to gather secondary data. The sample was chosen through purposive sampling according to particular criteria, yielding 69 observations from 23 firms over a period of three years. The results indicate that financial distress is notably influenced by profitability, while liquidity, sales growth, and firm size are not Additionally, leverage does not influence the connection between the independent variables and financial distress. These outcomes are anticipated to serve as a useful reference for companies and financial statement users in managing finances and making informed decisions.